THE DISPOSITIVE OF DIMENSION A STUDY OF SOCIOLOGY LITERATURE FROM NOVEL CINTA DAN KEWAJIBAN BY L. WAIRATA DAN NUR SUTAN ISKANDAR - Kumendong, Yeremia Serrian (LANTERN (Journal on English Language, Culture and Literature), 2013)
The Novel Love and duty is one of novel whom the Writer is Andrean Hirrata, it storied about woman teenager and her life. In this novel L. Wairata Nur sutan Iskandar described the struggle and work hard of Ani, and her spiritual experiences when se lived in Tihulale, Ambon. There are many conflicts in this novel. Those conflicts generate social aspect and become message in this novel. The purpose of this research is revealing the relationship of the element structure and social aspect from novel of Love and Duty. The analysis result of Edensor novel is there are moral value that we can find everyday, sincerity and compassion for other, the struggling of reaching dream, and dutiful to our parents Key word : Sociology Literature, Novel Cinta dan Kewajiban, dan L. Wairata dan Nur Sutan Iskandar